2021
DOI: 10.1002/iid3.534
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐testis antigen ACRBP expression and serum immunoreactivity in ovarian cancer: Its association with prognosis

Abstract: Introduction: Cancer testis (CT) antigens are attractive targets for cancer immunotherapy because of their expression restriction and immunogenicity. The acrosin binding protein (ACRBP) is a member of CT antigens. This study aimed to evaluate ACRBP expression and immunogenicity in ovarian cancer (OC). Methods:The expression level of ACRBP in OC tissues, normal ovarian tissues, and cell lines was detected via quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry. We determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Some poorly differentiated tumors, such as colorectal cancer, ovarian cancer, and glioma, were found to have higher OY-TES-1 expression than well-differentiated tumors or their adjacent tissues [ 10 , 11 , 15 ]. OY-TES-1 expression may be significantly higher in the tumors of ovarian cancer patients with shorter survival times and faster relapse than those with longer survival [ 24 , 25 ]. Higher expression of OY-TES-1 appears to be related to high cell proliferative activity, as supported by several in vitro experiments [ 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some poorly differentiated tumors, such as colorectal cancer, ovarian cancer, and glioma, were found to have higher OY-TES-1 expression than well-differentiated tumors or their adjacent tissues [ 10 , 11 , 15 ]. OY-TES-1 expression may be significantly higher in the tumors of ovarian cancer patients with shorter survival times and faster relapse than those with longer survival [ 24 , 25 ]. Higher expression of OY-TES-1 appears to be related to high cell proliferative activity, as supported by several in vitro experiments [ 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…OY-TES-1 was expressed both in distinct tissues of the fetus and adult, which indicates its potential as an autoantigen. It is believed that high OY-TES-1 expression or expression outside the normal location should be regarded as ectopic and a target of immunoreaction [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that CT23 is not only highly expressed in various tumors, but also presents detectable specific antibodies in the serum of tumor patients, while the serum of healthy individual is negative. 9 , 13–15 , 17 These results suggest that CT23 is immunogenic like many other CTAs. Therefore, in recent years, many scholars have explored the possibility of CT23 as a target for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 81%
“… 10 Some of experiments in vitro have confirmed that down-regulating CT23 can reduce cancer cell growth, prevent cancer cell migration and invasion, and elevate the expression of apoptosis-related proteins, thereby promoting cell apoptosis. 11 , 12 In patients with ovarian cancer, high expression of CT23 was associated with paclitaxel resistance, stage and chemotherapy sensitivity, shortened survival time and accelerated recurrence rate, 10 , 13 while in colorectal cancer patients, high expression of CT23 is also confirmed to be correlated with tumor invasion stage and histological grade. 15 Furthermore, the presence of CT23 antibodies in the serum of patients with various tumors, including ovarian cancer, colorectal cancer, liver cancer, and glioma, indicates that CT23 is immunogenic and can induce a specific immune response, 13–15 , 17 making it a potential diagnostic and therapeutic target in cancer.…”
Section: Introductionmentioning
confidence: 98%
“…В соматических тканях были обнаружены лишь следы мРНК OY-TES-1, тогда как в различных опухолях мРНК этого гена обнаруживалась с высокой частотой. Изучена экспрессия OY-TES-1 в мезенхимальных стволовых клетках [5], в клетках гепатоцеллюлярной карциномы [6], при раке яичников [7], раке молочной железы [8], показано влияние OY-TES-1 на процессы клеточного роста, клеточную миграцию, апоптоз, митоз и пролиферацию раковых клеток [5][6][7]. Иммуногистохимические исследования (ИГХ) и метод полимеразной цепной реакции (ПЦР) продемонстрировали полное отсутствие экспрессии OY-TES-1 в тканях здорового кишечника, здоровой печени и циррозной печени [6,9].…”
Section: Introductionunclassified